Analisis Kebijakan Pajak Penjualan Atas Barang Mewah (PPnBM) - Marshanda Anindhita Sulistianti; Raisha Awaluna Gani; Muhamad Sugilar (Institut Teknologi dan Bisnis (ITB) Semarang, 2026)
The implementation of Income Tax Article 22 on import activities plays a strategic role in securing state revenue and controlling international trade flows. However, corporate taxpayers frequently encounter substantial barriers regarding regulatory compliance and technical administrative procedures. This study aims to analyze the compliance level of corporate taxpayers concerning the collection and reporting of Income Tax Article 22 on import activities, while identifying the primary obstacles faced during the process. The research employs a qualitative descriptive method with a case study approach conducted at the Tax Allowance Office. Primary data were gathered through semi-structured interviews with corporate taxpayers and tax authorities, supplemented by secondary data from tax compliance reports and related documentation. The findings indicate that while formal compliance regarding timely reporting has significantly improved due to digital administrative transformations like the e-Bupot system, substantial challenges remain in material compliance. Corporate taxpayers routinely face difficulties in classifying import tariff codes accurately and interpreting the frequent updates to tax incentives. This study implies that the tax authority needs to intensify specialized socialization programs and optimize the integration of data systems between the Directorate General of Taxes and the Directorate General of Customs and Excise. These strategic improvements are crucial to minimizing administrative discrepancies and enhancing overall tax compliance.